Analisis Fiskal dan Inflasi pada Pertumbuhan Ekonomi dan Implikasinya terhadap Pengangguran - Arifin, Zainal; Barkah, Januar; Alam, Bambang Perkasa (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of fiscal policy represented by government expenditure together with inflation on economic growth in Indonesia during the 2007–2021 period. A quantitative approach was employed using the Ordinary Least Squares (OLS) method with EViews 12 software. Economic growth was used as the dependent variable, while government expenditure and inflation served as the independent variables. The results indicate that government expenditure and inflation simultaneously exert a significant influence on economic growth, as reflected by the Prob(F-statistic) value of 0.040772. However, the partial test shows that both independent variables have no significant effect on economic growth. Government expenditure exhibits a negative and insignificant relationship, whereas inflation shows a positive yet insignificant influence. These findings imply that the increase in government spending has not been fully directed toward productive sectors, particularly during the COVID-19 pandemic period. In addition, low inflation does not indicate strengthened aggregate demand. Overall, this study emphasizes the importance of synergy between fiscal policy and price stability in supporting sustainable economic growth in Indonesia.